THE PLACE OF SMALL BUSINESS IN THE NATIONAL ECONOMY AND ITS SIGNIFICANCE - Karimjonov Doniyorbek Ibrohimjon o’g’li (PT. Antis International Publisher, 2024)
The small business sector is an integral, objectively necessary element of any developed economic system, without which the economy and society as a whole cannot exist and develop normally. Although the indicator of any developed country consists of large corporations, the presence of strong economic power (large capital) largely determines the level of scientific, technical and production potential, the real basis of life in countries with a market economy system, small enterprises as the most common, dynamic and flexible form of business life. The main part of the national resources, which are the basis for medium and large businesses, are created and put into circulation in the small business sector. High flexibility and broad coverage of almost all sectors of the country's domestic market ensure the stability of economic development and contribute to the stability of the political climate.